Perbandingan Efektifitas Water Tepid Sponge dan Cool Patch terhadap Penurunan Suhu Tubuh Anak dengan Demam di Ruang Parkit Rumah Sakit QIM Batang - Nurul Atikah; Heri Susanto; Kurnia Wijayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Fever in children, if not properly managed, can lead to several negative effects such as excessive fluid loss through evaporation, dehydration, seizures, decreased consciousness, and even death if left untreated. Non-pharmacological interventions to reduce fever include water tepid sponge therapy and cool patch therapy. This study used a quasi-experimental design with a pretest and posttest three-group approach. Respondents were divided into three groups: water tepid sponge, cool patch, and control. Data were analyzed using the Wilcoxon test and the Mann-Whitney test. The Wilcoxon test showed a significance value of 0.000 in the Water Tepid Sponge group, 0.000 in the Cool Patch group, and 0.002 in the control group. The Mann-Whitney test showed no significant difference between the pre-test body temperature of the Water Tepid Sponge group and the control group (p = 0.063 > 0.05), while a significant difference was found in the post-test (p = 0.000 < 0.05). For the Cool Patch group, there was no significant difference in the pre-test compared to the control (p = 0.672), but a significant difference was found in the post-test (p = 0.001). The Mann-Whitney test comparing the pre-test and post-test temperature differences between the Water Tepid Sponge and Cool Patch groups showed a significance value of 0.000. The mean rank for temperature reduction in the Water Tepid Sponge group was 35,27, while in the Cool Patch group it was 17,73. Both Water Tepid Sponge and Cool Patch therapies have an effect on reducing fever in pediatric patients in the Parkit Ward of QIM Hospital Batang. Water Tepid Sponge therapy is more effective than Cool Patch therapy in reducing fever.